Acidification and high-temperature impacts on energetics and shell production of the edible clam Ameghinomya antiqua - Sebastián I. Martel; Carolina Fernández; Nelson A. Lagos; Fabio A. Labra; Cristián Duarte; Juan F. Vivanco; Claudio García-Herrera; Marco A. Lardies (Frontiers in Marine Science, 2022)
Warming and ocean acidification are currently critical global change drivers for marine ecosystems due to their complex and irreversible effects on the ecology and evolution of marine communities. Changes in the chemistry and the temperature of the ocean impact the biological performance of marine resources by affecting their energy budget and thus imposing energetic restrictions and trade-offs on their survival, growth, and reproduction. In this study, we evaluated the interplaying effects of increased p CO 2 levels and temperature on the economically relevant clam Ameghinomya antiqua , an infaunal bivalve inhabiting a wide distributional range along the coast of Chile. Juvenile clams collected from southern Chile were exposed to a 90-day experimental set-up emulating the current and a future scenario projeced to the end of the current century for both high p CO 2 /low-pH and temperature (10 and 15°C) projected for the Chilean coast. Clams showed physiological plasticity to different projected environmental scenarios without mortality. In addition, our results showed that the specimens under low-pH conditions were not able to meet the energetic requirements when increased temperature imposed high maintenance costs, consequently showing metabolic depression. Indeed, although the calcification rate was negative in the high- p CO 2 scenario, it was the temperature that determined the amount of shell loss. These results indicate that the studied clam can face environmental changes for short-term periods modifying energetic allocation on maintenance and growth processes, but with possible long-term population costs, endangering the sustainability of an important benthic artisanal fisheries resource.